Advances in Experimental Medicine and Biology
DOI: 10.1007/0-306-46830-1_8
|View full text |Cite
|
Sign up to set email alerts
|

Opsonophagocytosis Versus Lectinophagocytosis in Human Milk Macrophages

Abstract: Some important immunoprotective effects of human breast milk have been attributed to the presence of macrophages. We investigated the generation of superoxide anion (O2-) by monocytes and human milk macrophages after stimulation with opsonized and unopsonized zymosan in the absence and presence of mannose as an inhibitor to investigate lectinophagocytic and opsonophagocytic properties. Peripheral blood monocytes generated more O2- than human milk macrophages (417,4 + 79,1 nmol O2-/mg protein vs. 216,1 +/-15,1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Chemokinetic agents such as TNFα in human milk may aid in recruiting macrophages to mucosal sites of the recipient's alimentary tract [63]. The human milk macrophage appears lipid laden and has diminished respiratory burst patterns compared with blood monocytes after opsonized phagocytosis; however, when stimulated by opsonin-independent mechanisms, milk macrophages have greater respiratory burst than blood monocytes [147][148][149][150]. It is postulated that as the intestinal environment of the neonate offers only a small amount of opsonins (complement and immunoglobulin G [IgG]), such differentiation of lectinophagocytic properties of milk macrophages could render a greater advantage to the neonate [147].…”
Section: The Cellular Compartment Of Human Milk: Its Physiologic Relementioning
confidence: 98%
See 1 more Smart Citation
“…Chemokinetic agents such as TNFα in human milk may aid in recruiting macrophages to mucosal sites of the recipient's alimentary tract [63]. The human milk macrophage appears lipid laden and has diminished respiratory burst patterns compared with blood monocytes after opsonized phagocytosis; however, when stimulated by opsonin-independent mechanisms, milk macrophages have greater respiratory burst than blood monocytes [147][148][149][150]. It is postulated that as the intestinal environment of the neonate offers only a small amount of opsonins (complement and immunoglobulin G [IgG]), such differentiation of lectinophagocytic properties of milk macrophages could render a greater advantage to the neonate [147].…”
Section: The Cellular Compartment Of Human Milk: Its Physiologic Relementioning
confidence: 98%
“…These macrophages survive in the neonatal gut environment during at least the first postnatal week and appear ideally suited to secrete various growth factors and cytokines to the recipient newborn gut. As a source of growth factors, macrophages that are present in human milk may "prime" the gut for continued epithelial maturation and closure [31, 41,44,61,81,147,150,[152][153][154][155]. Cell-to-cell interactions appear to play an integral part in the maturation of the GI tract of newborns [156].…”
Section: The Cellular Compartment Of Human Milk: Its Physiologic Relementioning
confidence: 99%
“…It has been observed that the MN phagocytes of the colostrum present bactericidal activity against enteropathogenic Escherichia coli equivalent to that of MN and PMN phagocytes from serum, and that this activity is dependent on IgA acting with opsonins 13. On the other hand, the significance of previous opsonization is still controversial; one study has indicated that human milk macrophages can be stimulated by mechanisms independent of opsonins 14.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the supposed immunoprotective effect of colostrum leukocytes [12,36] and a higher and different glycosylation of casein GMP (glycomacropeptide) which could lead to a closer similarity with human GMP [2], in a first approach, it can be concluded that most of the interesting components are in the whey part of the colostrum. Considering, on the other hand, the potential of membrane microfiltration for the selective separation of milk particles [5,24,32], application of this technology to colostrum as already patented by Garcin et Paviot [7] appears to be an elegant way to prepare, in mild conditions of time and temperature, a high quality "serocolostrum" without blood red cells, somatic cells, fat globules, bacteria and casein micelles of which all the whey proteins and mainly the IgG could easily be specifically concentrated by membrane ultrafiltration.…”
Section: Introductionmentioning
confidence: 99%